Compliance Level and Stability of Micronutrients in Fortified Maize Flour in Tanzania - Abdulsudi Issa-Zacharia; Gudila Boniface Mareni (International Journal of Food Science)
Maize flour fortification was introduced in Tanzania in 2011 to address the risk of micronutrient deficiency to children, adolescents, and women of childbearing age. Fortified maize flours are processed by small-scale processors who are exempted from mandatory fortification. The current study is aimed at assessing the compliance and stability of fortified processed maize flour with zinc, iron, and folic acid by small-scale processors in comparison to the recommended Tanzania national standards (TZS 328). A total of 69 samples of fortified maize flour were collected at the point of production and retail outlets in Dar es Salaam and Morogoro municipalities, Tanzania. Micronutrients (zinc and iron) were analysed using microwave plasma atomic emission spectrometry (MP-AES), and folic acid was analysed using high-performance liquid chromatography (HPLC). The mean concentrations of micronutrient were significantly (p<0.05) higher at the production site compared to the retail outlet. The amount of iron, zinc, and folic acid in the samples at the production site was 27.17±1.63 mg/kg, 30.56±2.01 mg/kg, and 0.69±0.02 mg/kg, respectively, while it was 19.34±0.97 mg/kg, 21.71±1.50 mg/kg, and 0.49±0.02 mg/kg for iron, zinc, and folic acid, respectively, at the retail outlets. Only 31.6% of the assessed samples from production and 12.9% from retail outlets complied with the recommended national standard. The stability of iron, zinc, and folic acid for the fortified maize flour stored at room temperature (20-32°C) for six months was 95.8%, 96.9%, and 66.9%, respectively. Further investigation on the consistency performance of the dosifier and consistency training of working in the processing unit on the requirements of fortification standards should be done.